Suspension of soft magnetic materials using high Tc superconductors - Tsutsui, Yukio; Higuchi, Toshiro (Electrical engineering in Japan, 1996)
This paper describes a novel suspension technique using high Tc superconductors and magnetic materials. It was found for a field‐cooled superconductor and an adjacent magnetic material that the usual inverse relationship between the attractive magnetic force and gap distance reverts to a direct relationship for small gap length. Thus, stable, noncontact suspension is possible within a certain gap range. This phenomenon was found for even a soft magnetic material possessing minimal coercive force. Since remarkable reversals were observed for magnetic materials with diameters much smaller than that of the pinned area, it is considered that some of the pinned flux is subject to a gathering effect in the magnetic material. Stable, contactless suspension of a 180 g carbon steel weight under a high Tc superconductor was achieved using this technique.